Copper-Catalyzed Four-Component A3-Based Cascade Reaction: Facile Synthesis of 3-Oxetanone-Derived Spirocycles - Rongkang Zhang; Liliang Huang; Aiguo Gu; Huangdi Feng (Chemistry)
3-Oxetanone-derived spirooxazolidines represent a class of building blocks for accessing diverse saturated heterocycles, but their synthetic methods remain unexplored. Herein, we demonstrate a highly atom-economic approach for the synthesis of diverse 3-oxetanone-derived N-propargyl spirooxazolidines via a CuBr2/TFA co-catalyzed four-component A3-based cascade reaction of a 1,2-amino alcohol, a 3-oxetanone, a formaldehyde, and an alkyne. This strategy is characterized by a wide substrate range and excellent chemoselectivity. In addition, the synthesized spirocycles could also be easily converted into other valuable compounds, facilitating potentially useful synthetic applications.